Governança no terceiro setor : estudo em associações e fundações privadas sem fins lucrativos do segmento meio ambiente com atuação no Brasil - Lacruz, Adonai José (2017)
The objective of this PhD dissertation was to investigate the corporate governance influence on the donation to charity projects receipt in the third sector entities context operating in Brazil, from an agency theory perspective. This research gap was obs